The internet : an introduction to new media - Green, Lelia, 1956- (Oxford ; New York : Berg, 2010)
"Life without the internet, a very new technology, seems almost unimaginable for most people in western nations. Today the internet is intrinsic to media and communications, entertainment, politics, defence, business, banking, education, and administrative systems, as well as to social interaction. The Internet disentangles this extraordinarily complex information and communication technology from its place in our daily lives, allowing it to be examined anew" "Technology has historically been shaped by governmental, military, and commercial requirements, but the development of the internet is increasingly driven by its users. You Tube, Facebook, Twitter, Flickr, and many other emerging applications are shifting the way we express ourselves, communicate with our friends, and even engage with global politics. At the same time three-quarters of the world's population remain effectively excluded from the internet" "Packed with case studies drawn from around the world, The Internet presents a clear and up-to-date introduction to the social, cultural, technological, and political worlds this new media form is creating"--BOOK JACKET.
Introduction -- History -- Policy -- The digital divide -- Customising the internet -- Regulation and legislation : pornography and cyber stalking -- The public sphere -- Community -- Internet in family life -- Conclusion.
Bibliografische referenties ; glossarium ; index
Keywords: Computers and civilization; Information society; Internet -- Social aspects